DYNAMICS OF ANTHROPOMETRIC INDICATORS OF INFANTS WITH MALNUTRIRION - Kholmatova, Нурхон; Xakimov, Шаробиддин (International Journal of Scientific Pediatrics, 2025)
Relevance. Protein-energy malnutrition (PEM) is a condition characterized by an imbalance of proteins and energy in the body, affecting its functions and leading to adverse outcomes, including mortality among children. Identifying children suffering from PEM and those at risk is an important first step in providing them with effective treatment and support. Objective. The aim of the study was to examine the main anthropometric indices of infants with protein-energy malnutrition depending on clinical and anamnestic data as well as the severity of the pathology. Materials and Methods. The study was conducted at the Regional Multidisciplinary Children’s Clinical Hospital in Andijan. The study included data from 135 children diagnosed with protein-energy malnutrition (PEM), whose anthropometric indicators were analyzed according to the degree of the condition. Results. This study examined the anthropometric indicators of children with various degrees of PEM. Based on the data from 135 children, the analysis showed a predominance of girls among the affected and a higher prevalence in the age group of 7–12 months. The study distinguished between prenatal and postnatal forms of PEM, which differ in clinical features. Prenatal forms of PEM are often associated with intrauterine growth retardation and exhibit differences in anthropometric indicators such as body weight, body length, and chest circumference. Conclusion. The results of this study confirm the importance of anthropometric methods in clinical practice for the diagnosis and treatment of protein-energy malnutrition in children. Early detection and a comprehensive approach to PEM management can significantly improve children’s health and prevent long-term adverse consequences. The study of anthropometric data contributes to better diagnosis and treatment of PEM in children.